Strategi Menumbuhkan Minat Baca Pada Taman Bacaan Masyarakat Inara Desa Kubang Jaya Kecamatan Siak Hulu Kabupaten Kampar : Strategi Menumbuhkan Minat Baca Pada Taman Bacaan Masyarakat Inara Desa Kubang Jaya Kecamatan Siak Hulu Kabupaten Kampar - Yasin Setiawan; Deliza Zakir; Sodirin (Jurnal Gema Pustakawan, 2023)
One effort that can effectively foster people's interest in reading is through TBM (Community Reading Gardens) activities. This research aims to find strategies to foster interest in reading through activities, especially in the Dusun IV community, Kubang Jaya Village, Kampar Regency. The study data in this research includes literature data, field observations and information from sources consisting of community leaders, youth, parents, early childhood (preschool and kindergarten), elementary and middle school students and equivalent, as well as high school students and equivalent. Theoretical data was extracted through various previous research and supporting references, as well as expert information (librarians and TBM activists in Riau Province). Through a qualitative approach using SWOT analysis, several strategies were found that could be implemented, namely: (1). Collecting data on community environmental conditions for the development of a reading environment, (2). Organizing book reading activities and story competitions, (3). Holding book review competition activities with the TBM Forum, and (4). Organizing fairy tale activities. The results of the research show that to increase people's reading interest in Dusun IV, Kubang Jaya Village, Kampar Regency, it is necessary to implement these four strategies in an integrated program with TBM Inara as the center for activities to increase reading interest in the area.